TIR8/SIGIRR is an Interleukin-1 Receptor/Toll Like Receptor Family Member with Regulatory Functions in Inflammation and Immunity - Riva, Federica (Frontiers Media S.A., 2012)
Interleukin-1R like receptors (ILRs) and Toll Like Receptors (TLRs) are key receptors of innate immunity, inflammation, and orientation of the adaptive response. They belong to a superfamily characterized by the presence of a conserved intracellular domain, the Toll/IL-1R (TIR) domain, which is involved in the activation of a signaling cascade leading to activation of transcription factors associated to inflammation. The activation of inflammatory responses and immunity by ILRs or TLRs signaling is potentially detrimental for the host in acute and chronic conditions and is tightly regulated at different levels by receptor antagonists, decoy receptors or signaling molecules, and miRNAs. Recent evidence suggests that the ILRs family member TIR8 (also known as SIGIRR) is a regulatory protein acting intracellularly to inhibit ILRs and TLRs signaling. In particular, current evidence suggests that TIR8/SIGIRR dampens TLRs-mediated activation and inhibits signaling receptor complexes of IL-1 family members associated with Th1 (IL-18), Th2 (IL-33), and Th17 (IL-1) differentiation. Studies with Tir8/Sigirr-deficient mice showed that the ability to dampen signaling from ILRs and TLRs family members makes TIR8/SIGIRR a key regulator of inflammation. Here, we summarize our current understanding of the structure and function of TIR8/SIGIRR, focusing on its role in different pathological conditions, ranging from infectious and sterile inflammation, to autoimmunity and cancer-related inflammation.